Time tO last ChemotherApy and death in ovaRian cancEr patients: TO CARE/MITO 42 study, a retrospective analysis of italian MITO centers - Scotto, Giulia; Galatà, Anna; Fruscio, Robert; Besana, Giulia; Landoni, Fabio; Sgro, Luca; Testi, Alessandra; Borella, Fulvio; Cormio, Gennaro; Gianciotta, Mariangela; Arezzo, Francesca; Maiorano, Brigida Anna; et al. (Frontiers in Oncology, 2025)
IntroductionThe European Society for Medical Oncology (ESMO) 2021 Guidelines contraindicate the administration of chemotherapy in the last month of patients’ life. The main objective of this multicenter observational retrospective study was to calculate the time elapsed between the date of the last chemotherapy and the date of death of patients with ovarian cancer. The secondary objectives were to identify any factors associated with a greater probability of receiving chemotherapy in the end of life.MethodsOvarian cancer patients operated between 2010 and 2020 in the participant Italian centers were enrolled. Only deceased patients whose date of death and date of last chemotherapy were known were included.Results603 women from 10 Italian centers were included. One patient out of four (25.7%) received chemotherapy in the last month of life. The median survival from the last chemotherapy was 66 days. Patients with a neutrophil/lymphocyte ratio ≥5, with high C-reactive protein at the start of the last line and patients dying in hospital compared to hospice/palliative care at home were more likely to undergo chemotherapy at the end of life (p<0.001, p=0.05 and p<0.001 respectively). Being treated in Northern Italy reduces the chance of receiving chemotherapy at the end of life in comparison with Center-South (p<0.001), as well as being enrolled in at least one clinical protocol (p=0.027).DiscussionThe TO CARE/MITO 42 study is a snapshot of the Italian practice in which there are still disparities in the treatment of patients at the end of life. A prospective observational study could provide useful elements for early identification of patients who would not benefit from a further line.